Wurfspezifische Wahrnehmungs- und Antizipationsprozesse des Handballtorwarts - Hatzl, T. (1998)
Despite of the incontestable importance of selective perception and anticipation there is a vast deficit in the scientific research on these psychomotor abilities. Which characteristics of the throwing movement can help the keeper to determine the future direction of a fast throw out of short and medium distances early enough to process the optical information and to react in an appropriate way? The author first tries to put in concrete terms the meaning and significance of 'anticipation'. The anatomical and neurophysiological foundations of selective attention and anticipational information processing are examined and some important theories of the perceptual psychology are discussed. A summary of respective findings in the field of sports games with demands similar to hand-ball (like tennis, baseball or volley-ball) gives further explanations to strategies of information-gathering of the keeper in hand- ball. In the empirical part the author tries to work out some distinctive marks of jumped throws to the left and to the right side of the goal by the means of a 3D-motion-analysis. Therefore, 11 hypothesis are defined (basis: literary research, interviews with 23 goal-keepers, personal experience of the author as a former keeper in hand-ball). The statistical analysis suggests the possible relevance of the following elements for an early decision of the goal-keeper: the direction of the system hand-ball during the final part of the throw; the angles of the hip- and of the shoulder-axis; the width of shoulders visible to the keeper; and the lateral distance of the ball to the trunk early in the throwing movement. The presented method is supposed to be qualified to ascertain possible criteria of observation also for other specific variations of throws.